2014
DOI: 10.1007/s10495-014-1044-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel oxaliplatin derivative, Ht-2, triggers mitochondrion-dependent apoptosis in human colon cancer cells

Abstract: Ht-2 is a novel oxaliplatin derivative previously identified in a compound screen performed by our laboratory. In the present study, we evaluated the antitumor effects of Ht-2 and investigated its underlying mechanism of action. Ht-2 exhibited anti-tumor activity and demonstrated low cytotoxicity in normal cells in vitro. The IC50 of Ht-2 was 2-10-fold lower than oxaliplatin in all of the cancer cell lines tested except MCF-7 cells, whereas, the value was threefold higher than cisplatin or oxaliplatin in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, this increase in DCF and mito-SOX was partially reversed when succinate accumulation was reduced. As an ROS marker, DCF-DA is used to assess oxidative stress [[72], [73], [74]], though there are some limitations to this technique. For example, DCF fluorescence cannot be used as a direct measure of H 2 O 2 , and is prone to multiple artifacts and artifactual amplification in ROS analysis [75].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this increase in DCF and mito-SOX was partially reversed when succinate accumulation was reduced. As an ROS marker, DCF-DA is used to assess oxidative stress [[72], [73], [74]], though there are some limitations to this technique. For example, DCF fluorescence cannot be used as a direct measure of H 2 O 2 , and is prone to multiple artifacts and artifactual amplification in ROS analysis [75].…”
Section: Discussionmentioning
confidence: 99%
“…Many existing first-line chemotherapeutics exploit the stress-induced death mechanism of cancer cells, 48 although there is often limited selectivity between cancer and noncancer cells. 49,50 Our recent study also showed that a cationic hydrophobic cyclometalated iridium complex can induce endoplasmic reticulum stress and apoptosis in cancer cells. 51 In this study, we demonstrated that 6 can induce a significantly higher level of ROS in cancer cells; thus, 6 displays a higher selectivity in killing cancer cells than normal cells.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Because of their rapid growth, frequent cell divisions, and active preparation for metastasis, cancer cells are subject to metabolically challenged conditions and are significantly reliant on ROS-response pathways, which can lead to the increased sensitivity of cancer cells to stress-inducing treatments, compared to normal cells. Many existing first-line chemotherapeutics exploit the stress-induced death mechanism of cancer cells, although there is often limited selectivity between cancer and noncancer cells. , Our recent study also showed that a cationic hydrophobic cyclometalated iridium complex can induce endoplasmic reticulum stress and apoptosis in cancer cells . In this study, we demonstrated that 6 can induce a significantly higher level of ROS in cancer cells; thus, 6 displays a higher selectivity in killing cancer cells than normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the internalized oxaliplatin can induce an intracellular H 2 O 2 generation, via NOXs activation and SODs‐mediated superoxide anion (O 2 ·− ) dismutation. Fortunately, H 2 O 2 also is the substrate of Fenton's reaction.…”
Section: Methodsmentioning
confidence: 99%